Pengaruh Pemadatan dan Substitusi Bubur Kertas terhadap Kuat Tekan Batako Ringan Struktural Dinding - Muhammad Riswandy; Alfisyahrin Alfisyahrin; Mhd. Arief Diana; Michel Kasaf; Ari Juanda (Yayasan Literasi Sains Indonesia, 2026)
This study analyzes the impact of compaction levels and paper pulp ratios on the compressive strength of papercrete blocks. The objective is to develop a lightweight building material that meets structural strength standards based on SNI 03-0348-1989. The base formulation combines cement and sand in a 1:3 ratio, with the sand volume substituted by paper at variations of 80%, 90%, and 100%. Density engineering was conducted by compressing the initial mixture volumes of 120%, 130%, 140%, and 150% into a standard size of 5 cm x 10 cm x 20 cm. Mechanical performance testing involved single blocks, paired blocks bonded with a 1 cm mortar joint, and conventional red bricks as a control comparison. Experimental results demonstrate that most papercrete variants qualify as structural materials within classes II, III, and IV. Only the 120PB100 sample failed to meet the standard classification. Interestingly, the standard red brick did not qualify for any strength class under the SNI framework. The highest mechanical performance was achieved by the 140PB80 variant, yielding a single-block compressive strength of 70.139 kg/cm². However, when evaluated in a paired formation, the strength of this 140PB80 sample reduced by 29.87% to 49.190 kg/cm².